Understanding Human Potential In The Ai Era: Implications For Financial Management Practices In Micro, Small And Medium Enterprises - Bilqis Tarwiyah (Universitas 45 Surabaya, 2023)
This research investigates the implications of the AI era on financial management practices in Micro, Small, and Medium Enterprises (MSMEs). The study aims to comprehend the evolving landscape of human potential utilization amidst technological advancements. Employing a qualitative approach, a model is developed to explore the intricate interplay between AI integration and human capital in financial management within MSMEs. Sampling techniques involve purposive sampling of MSMEs representatives knowledgeable in financial management and AI integration. Data analysis is conducted through thematic analysis, delving into patterns and themes emerging from interviews and case studies. Results reveal nuanced insights into the role of human potential in navigating the AI-driven financial ecosystem of MSMEs, shedding light on strategies for leveraging human-AI collaboration for enhanced financial performance.